Writing in real time : emergent poetics from Whitman to the digital - Jaussen, Paul (Cambridge University Press, 2017)
From Walt Whitman to the contemporary period, the long poem has been one of the more dynamic, intricate, and yet challenging literary practices of modernity. Addressing those challenges, Writing in Real Time combines systems theory, literary history, and recent debates in poetics to interpret a broad range of American long poems as emergent systems, capable of adaptation and transformation in response to environmental change. Due to these emergent properties, the long poem performs essential cultural work, offering a unique experience of history that remains valuable for our rapidly transforming digital age. Moving across a broad range of literary and theoretical texts, Writing in Real Time demonstrates that the study of emergence can enhance literary scholarship, just as literature provides unique insights into emergent properties, making this book a key resource for scholars, graduate students, and undergraduate students alike.
Keywords: American poetry -- History and criticism.; Poetics -- History.; Poésie américaine -- Histoire et critique.; Poétique -- Histoire.; LITERARY CRITICISM -- Poetry.; American poetry; Poetics; Literature: history & criticism.; Literary studies: general.; Literary studies: c 1900 to c 2000.; North America.; English.; Literary studies: poetry & poets.; United States of America, USA.; Literature.; Criticism, interpretation, etc.; History